The Issues of Palestine and Algeria on the Delay of NATO’s Formation, 1948–1949: A Study on British International Negotiations - Hussain, Norasmahani; Mohd Sharif, Mohd Farid (Journal of Al-Tamaddun, 2025)
The North Atlantic Treaty Organisation (NATO) is a military pact founded on 4 April 1949 in Washington D.C. Initially, it was comprised of 12 members committed to containing Soviet encroachment during the Cold War. Since its formation, NATO has expanded to include 32 members. The original members included seven founding countries, namely, Britain, France, the Netherlands, Belgium, Luxembourg, the United States (U.S.), and Canada, and five invited countries, which were Italy, Norway, Portugal, Iceland, and Denmark. The drafting of this Atlantic military pact involved over a year of negotiations, from March 1948 to March 1949. Previous studies indicate that the process was lengthy primarily due to the issue of Italian membership, which caused delays and rescheduling of the signing ceremony from 1 February 1949 to the first week of April 1949. In addition to the Italian membership issue, this study argues that Palestine and Algeria, though peripheral to the NATO negotiations, contributed to the delay in NATO’s formation. By analysing British Foreign Office Papers (FO 371) and the Foreign Relations of the United States (FRUS), this study reveals the disagreement between Britain and the U.S. over these ‘stray-stone’ countries during the NATO negotiation period. This study is significant because it highlights how seemingly unrelated geopolitical situations can substantially impact major international developments. It demonstrates how the resulting delay was resolved, offering a valuable case study of the unpredictable nature of international negotiations from the perspective of Britain.